A colorimetric field method to assess the authenticity of drugs sold as the antimalarial artesunate. - Green, MD; Mount, D; Wirtz, R; White, N (2000)
Artesunate is the most widely used of the artemisinin derivatives. These drugs are being used increasingly throughout the tropical world, and are an essential component of the treatment of multi-drug resistant malaria. The recent and widespread appearance of counterfeit artesunate tablets in several countries in Southeast Asia poses a serious threat to health in this region. We have developed a simple, inexpensive colorimetric test to determine artesunate authenticity in tablets. The test is based on a reaction between an alkali decomposition product of artesunate and a diazonium salt, fast red TR (FRTR). The appearance of a yellow color indicates the presence of artesunate. The specificity of the test is dependent on the pH of the reaction. Among other antimalarials tested, (i.e. artemisinin, artemether, chloroquine, quinine, primaquine, sulfadoxine, and pyrimethamine) only artesunate produced a positive color reaction at pH 4. The assay requires only 1% of the total weight of a standard tablet containing 50 mg of artesunate and can be completed within 10 min. The method was tested on six genuine artesunate tablets and six counterfeit artesunate tablets obtained in Southeast Asia. The average amount of artesunate in the genuine tablets was determined to be 50.8 +/- 2.9 mg while the counterfeit tablets were found to contain no artesunate.